EFFECT OF SECTION THICKNESS ON NODULAR GRAPHITE FORMATION AND MECHANICAL PROPERTIES OF DUCTILE CAST IRON - Moch Chamim; Edi Sarwono; Haikal; Margono (Universitas Negeri Surabaya, 2026)
This study investigates the effect of section thickness on the microstructure and mechanical response of Ductile Cast Iron (DCI) using specimens with thicknesses of specimen 20, 40, and 60 mm. Optical microscopy reveals a ferrite-pearlite matrix with spherical graphite, where the graphite nodules exhibit a tendency toward larger size and greater heterogeneity with increasing section thickness. The measured nodule diameters are approximately 17-20 µm (20 mm), 21-22 µm (40 mm), and 15-26 µm (60 mm), indicating thickness-driven changes in solidification/cooling conditions that promote graphite hardening in thicker sections. Mechanical testing shows a consistent decrease in hardness with increasing thickness: 246.8 VHN (specimen 20 mm), 226.75 VHN (specimen 40 mm), and 204.8 VHN (specimen 60 mm). Impact test results show a non-monotonic trend, increasing from 0.02 (specimen 20 mm) to 0.049 (specimen 40 mm) and slightly decreasing to 0.045 (specimen 60 mm). The highest impact value at specimen 40 mm indicates an optimal balance between matrix hardness and toughness at intermediate thicknesses, while the slight decrease at specimen 60 mm despite the lower hardness may be related to increased graphite size heterogeneity and microstructural nonuniformity in thicker sections. Overall, thickness significantly affects graphite morphology and the hardness toughness trade off in DCI, with 40 mm sections providing the most favorable toughness in this data set.